THE EFFECTIVENESS OF GIVING BADUY HONEY ON INCREASED HEMOGLOBIN IN PREGNANT WOMEN AT UPT PUSKESMAS DTP SAKETI - Nuranissa, Hana; Yuningsih, Sukarni Setya (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: Anemia in pregnancy is usually caused by a lack of nutritional intake during pregnancy where the need for iron increases. One effort is to consume natural ingredients such as honey. Honey has many ingredients that are beneficial for the body, especially pregnant women, where 100 grams of honey contains 0.42 mg of fe/iron and 2 micrograms of folate, 0.5 mg of vitamin C. Research purposes: To find out the benefits of giving Baduy honey in increasing hemoglobin levels in pregnant women. Research methods: This type of research is quantitative research, The research method used by the author is a quasi-experimental method (Quasi Experiment).